Dental Care: Need, Methods, Current Status And Role Of Pharmacist - Aphale, Sanjivani (International Journal of Pharmaceutical & Biological Archive, 2010)
Mouth is a mirror that can reflect the health of the rest of your body. Numerous recent studies investigating the mouth-body connection have suggested an association between oral health and general health. In this paper a brief account on oral and dental hygiene is given and highlighted is the need to take more care by a pharmacist. Proper dental hygiene is characterized by healthy gums and teeth, fresh breath and absence of any pain whereas toothache, bad breathes, accumulation of plaque and tartar, may be indications of improper dental hygiene. Various complications due to negligence or improper dental hygiene and the measures taken to prevent and cure them have been enlisted in brief. In the study we conducted a general Survey in the region of Pune by devising a questionnaire and understanding how much importance is being given to the subject of dental hygiene and understanding lacunae as to where a pharmacist can help. Although the practice of pharmacy is not followed by the pharmacists in India as it is followed in the western countries, the fact that today’s pharmacist should play an extended role of seven star pharmacists has been accepted in India. The retailer of drugs has to play a role of care giver, manager of health resources as well as an educator. This survey reveals a fact that there are many things a pharmacist can do to educate common people about dental care and to improve their dental hygiene.